2011
DOI: 10.1007/8904_2011_78
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration with Brain Iron Accumulation on MRI: An Adult Case of α-Mannosidosis

Abstract: Case: A 34-year-old woman was referred to our hospital with progressive movement disorders and neurodegeneration with brain iron accumulation and enlargement of the frontal diploe on the MRI. Metabolic testing revealed that she had a-mannosidosis (AMD), a lysosomal storage disorder.Background: AMD is a rare genetic disorder that causes a-mannosidase deficiency resulting in lysosomal accumulation of undigested oligosaccharides. The symptoms of AMD consist of facial and skeletal deformities combined with progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The three patients here described, MD-137 ( FUCA1 ), MD-020 ( GLB1 ), and MD-153 ( TPP1 ), suffered from lysosomal diseases. Additionally, a subject with α-mannosidosis, also a lysosomal storage disease, who presented hypointensity signals in the GP was published [ 48 ]. Taken together, NBIA on MRI seems not to be so rare in some lysosomal disorders, especially in GM1-gangliosidosis, since so far, five unrelated cases are known (including our proband).…”
Section: Discussionmentioning
confidence: 99%
“…The three patients here described, MD-137 ( FUCA1 ), MD-020 ( GLB1 ), and MD-153 ( TPP1 ), suffered from lysosomal diseases. Additionally, a subject with α-mannosidosis, also a lysosomal storage disease, who presented hypointensity signals in the GP was published [ 48 ]. Taken together, NBIA on MRI seems not to be so rare in some lysosomal disorders, especially in GM1-gangliosidosis, since so far, five unrelated cases are known (including our proband).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the accuracy of automated brain morphometry methods is also important for the comprehension of the pathophysiology of neurological and neuropsychiatric disorders with basal ganglia involvement, such as Parkinson's syndrome, Huntington's disease, dystonia, various tremor forms, Tourette's syndrome and schizophrenia ( Utter and Basso, 2008 ). There is substantial controversy in the literature about the magnitude, directionality and neurobiological interpretation of basal ganglia structural changes in both healthy ageing and in diseased brain ( Koolschijn et al, 2009; Mars et al, 2011; Zoons et al, 2012 ). The majority of these studies assessed basal ganglia anatomy using T1-weighted (T1w) imaging data, which turned out to be methodologically challenging ( Wonderlick et al, 2009; Babalola et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, only small numbers of patients have been described and/or Fe accumulation is inconsistent, and neuropathological proof of Fe accumulation is lacking in these disorders [2]. Caution is necessary in the interpretation of T2/T2*-weighted MRIs as has been shown for mannosidosis; this disorder was considered in the differential diagnosis of NBIA [257] but a semiquantitative analysis in a group of mannosidosis patients showed that the hyposignal appearance of the deep gray matter is only relative and rather caused by an increased signal from the surrounding white matter [258].…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 99%